Youth Gangs and Victimization: An Investigation of the Impact of Gang Dynamics on Experiences of Victimization. Issue 9 (2nd September 2022) - Leverso, John; K. O'Neill, Kate
ABSTRACT: Studies comparing gang members to similarly situated non-gang members find youth gang involvement is positively associated with experiencing simple and aggravated assault (i.e., violent victimization). This study expands on those studies by using data on gang dynamics from the Denver Youth Survey and bringing theory and concepts directly related to street gangs to the analysis of the relationship between gang membership and different forms of victimization. We focus on specific mechanisms – such as gang organization, centrality, leadership roles, identity, and tenure – that inform gang member behaviors while controlling for risky behaviors and personal histories. Findings indicate (1) gang organization is positively associated with both simple and aggravated assault victimization; (2) gang centrality is positively associated with aggravated assault victimization; and (3) being the leader of a gang is negatively associated with aggravated assault victimization. We discuss the implications of these results using a gang-informed framework.